The lived experiences and social support needs of first-time mothers at health care facilities in the City of Tshwane, South Africa - Mmajapi E.T. Masala-Chokwe; Tendani S. Ramukumba (AOSIS, 2017)
Background: Social support refers to the assistance people receive from others, and it is divided into four types of support. Given the increasing mortality and morbidity rates of mothers and neonates postpartum, this study intended to determine whether the social support needs of the first-time mothers were met after early discharge from health care facilities. Objectives: The objective of the study was to explore the lived experiences and social support needs of the first-time mothers after an early discharge from health care facilities in the City of Tshwane, Gauteng. Method: A qualitative explorative study was conducted to explore the lived experiences and social support needs of the first-time mothers. The population were first-time mothers who had a vaginal delivery and were discharged within 6-12 hours of delivery from health care facilities. Purposive sampling was performed and 14 semi-structured interviews were conducted, with those mothers who came for the prescribed three postnatal check-ups at the three health care facilities identified according to maternity services provided. Saturation of data for the three health care facilities was reached at the 14th interview. Data analysis was performed using the hermeneutic interpretive approach. Results: Almost all participants had completed grades 11 or 12, but most were unemployed. The needs identified included the need for social support, lack of confidence, knowledge and skill to care for themselves and their newborn babies after early discharge. Conclusion: There is need to identify alternative types of social support for the first-time mothers, to ensure a normal adjustment to motherhood.